Hemingway : the 1930s through the final years - Reynolds, Michael (New York W. W. Norton, 1997)
Michael Reynolds was the supreme biographer of Ernest Hemingway. HBO$1 (Bs film concentrates on Hemingway$1 (Bs years with his third wife, the adventurous journalist Martha Gellhorn. This book brings together Reynolds$1 (Bs Hemingway: The 1930s and Hemingway: The Final Years.s
Keywords: Journalists; War and literature; Last years of a person's life